Antimicrobial flavonoids and their role in plant and animal interactions - Moheisen, Hassan Mahmoud Hassan (Journal of medical and pharmaceutical sciences, 2017)
Flavonoids are ubiquitous in photosynthesising cells and are commonly found in fruit, vegetables, nuts, seeds, stems, flowers, tea, wine, propolis and honey. For centuries, preparations containing these compounds as the principal physiologically active constituents have been used to treat human diseases. One of the undisputed functions of flavonoids and related polyphenols is their role in protecting plants against microbial invasion. This not only involves their presence in plants as constitutive agents but also their accumulation as phytoalexins in response to microbial attack. Because of their widespread ability to inhibit spore germination of plant pathogens, they have been proposed also for use against fungal pathogens of Man. It is now generally accepted that flavonoids, along with other plant polyphenols, play a role in protecting plants from both insect and mammalian herbivory. In recent years, attention has been mainly centered on simple phenolic constituents or on the polymeric flavolans or pro-anthocyanidins, but some research has been concerned with low molecular weight flavones, flavonols and isoflavones. For example, three glycoflavones schaftoside, isoschaftoside and neoschaftoside have been identified in the phloem sap of rice plants, where they act as sucking deterrents to the pest insect, the brown plant hopper Nilaparvata lugens. The purpose of the present review is to discuss recent developments in the biochemistry and medicinal aspects of the flavonoids. It is already well established that flavonoids make some contribution to disease resistance, either as constitutive antifungal agents or as phytoalexins. There is also increasing evidence that some flavonoids, and especially the flavolans or proanthocyanidins, provide defence against herbivory and some recent experiments in plant-animal interactions will also be mentioned.